A Treatise on the Theoretical Basis of Research on the Organizational Culture of a Police Organization - Radoslav Ivančík (Belügyi Szemle, 2021)
In recent years, we can meet more and more often in various professional publications, magazines, conferences, but also in various reports in the media the term organizational culture. The fact is that gradually more and more organizations are dealing with issues of organizational culture because they have understood that organizational culture plays an important role in the life of organizations. And not only in formulating organizational strategy, setting goals, or making decisions, but also in fulfilling their mission, creating their image and overall functioning in today's dynamic times affected by deepening globalization. That is also why the author, in his research, deals with organizational culture, specifically, in the presented article he examines police culture. The author characterizes police culture as a specific type of organizational culture that fulfils important functions and missions in terms of police functioning. By analogy with other types of organizations, the author defines police culture as a set of socially typical views, attitudes, norms, and values that determine models of police behaviour, relations to society and the police organization. He points out that despite the generally similar characteristics with other cultures of the organization, there are certain specifics that distinguish the police culture from other organizations. It gives it uniqueness. It should be a priority for every organization to have a good organizational culture aimed at maximum efficiency and success. For this reason, it is important to know its current state by research and to evaluate its positive and negative aspects. The article deals with the theoretical basis of understanding key concepts such as organization, culture, subculture, and organizational culture. At the same time, it presents the theoretical basis for the study of this phenomenon in the environment of the Police Force.